It is okay to take the inverse of both side given that you remember to exclude the value that make the denominator zero which is in this case r=-1
Answer:
23.04 m^2
Step-by-step explanation:
The volume of a prism is base * height. In the case of a triangular prism, you need to find the area of the base first (aka the triangle).
The area of a triangle is base * height / 2. Since we have the values for those we can substitute the values into the formula and solve.
2.4 * 3.6 / 2 = 3.84.
Now multiply that by height of the prism, which is 6, and we get 23.04 m^2.
Hope this helps!
I think you would have 3 1/2 yards left (3 2/4 simplified)
Answer:
(f of)(-2) = -65
Step-by-step explanation:
<u>Set up (f of)(-2)</u>
(f o f)(-2) = f(f(-2))
<u>Once you get (fof)(-2) you then have f(#)</u>
f(6(-2) + 1) = f(-11)
6(-11) + 1 = -66 + 1 = -65